Mindfulness-based Stress Reduction in Pregnancy: an App-Based Programme to Improve the Health of Mothers and Children (MINDFUL/PMI Study) - Lenz, Bernd; Eichler, Anna; Schwenke, Eva; Buchholz, Verena N.; Hartwig, Charlotte; Moll, Gunther H.; Reich, Karin; Mühle, Christiane; Volz, Bernhard; Titzmann, Adriana; Beckmann, Matthias W.; Heinrich, Hartmut; Kornhuber, Johannes; Fasching, Peter A. (Geburtshilfe und Frauenheilkunde, 2018)
Unfavourable intrauterine environmental factors increase the risk of delivery complications as well as postpartum developmental and behavioural problems in children and adolescents with ongoing effects into older age. Biomarker studies show that maternal stress and the use of alcohol and tobacco during pregnancy are associated with a higher intrauterine testosterone exposure of the child. The antenatal testosterone load, in turn, is a risk factor for lasting adverse health effects which extend into adulthood. A 15-week, mindfulness-oriented, app-based programme for the reduction of stress as well as for the reduction of alcohol and tobacco use in pregnant women is established. In the monocentre, prospective, controlled, and investigator-blinded MINDFUL/PMI (Maternal Health and Infant Development in the Follow-up after Pregnancy and a Mindfulness Intervention) study, pregnant women carry out the programme. Its effect on antenatal testosterone exposure of the child is examined by assessing the index/ring finger length ratio and other biomarkers in the 1-year-old children. In addition, the programmeʼs effects on self-regulation, the developmental status and the mental health of the children at the age of one year will be investigated. Additional aspects of the course of the pregnancy and delivery represent exploratory study objectives. This longitudinal study project is intended to improve the understanding of the impact of intrauterine environmental factors on early childhood development and health. Maternal stress as well as alcohol and tobacco use during pregnancy are modifiable factors and represent potential preventive targets.
Keywords: pregnancy; stress; alcohol; tobacco; testosterone; 2D : 4D; index/ring finger length ratio; mindfulness